Anaerobic digestion performance and microbial community structures in biogas production from whiskey distillers organic by-products. (December 2020) - Jackson, Stephen A.; Kang, Xihui; O'Shea, Richard; O'Leary, Niall; Murphy, Jerry D.; Dobson, Alan D.W.
Abstract: By-product and residue management are significant economic and environmental considerations in whiskey production. Incorporation of sustainable production methods in the industry can reduce costs in the areas of energy consumption and waste disposal and lessen environmental impacts via reduced greenhouse gas emissions. Circular economy opportunities for waste valorisation are possible also, such as anaerobic digestion of process effluents with high organic loads to produce high quality biogas for use in generation of thermal energy, electricity and transport biofuel. In this study lab-scale anaerobic digestion of whiskey distillery waste streams was trialled at mesophilic and thermophilic temperatures. Biogas production was assessed while monitoring process parameters and the microbial communities at different stages of reactor operation were described. Syntrophic acetate-oxidation appeared to be a significant process at mesophilic temperatures but not at thermophilic operation. Both hydrogenotrophic methanogenesis and acetoclastic methanogenesis appear to be important methanation processes under both temperature regimes. Highlights: In mesophilic digestion acetate-oxidation is important for methanogenesis. In thermophilic digestion hydrogenotrophic methanogenesis is the primary pathway. Bacterial population dynamics are responsible for inhibition of methanogenesis. Neutralization of the liquid fractions prior to feeding could enhance performance.